Two artificial neural networks meet in an online hub and change the future (Of competition, market dynamics and society) - Ezrachi, A; Stucke, ME (Oxford Legal Studies Research Papers, 2017)
In the future, one may imagine a new breed on antitrust humor. Jokes might start along the following lines: “Two Artificial Neural Network and one Nash equilibrium meet in an online (pub) hub. After a few milliseconds, a unique silent friendship is formed…” Back to the present; we are not sure how this joke might end. Nor can we estimate how funny future consumers would find it. We can, however, explain, at present, how technological advancements have changed, and will continue to change, the dynamics of competition and subsequently the distribution of wealth is society. How algorithms may be used in stealth mode to stabilize and dampen market competition while retaining the façade of competitive environment. That tale is at the heart of this paper.